Adapting a guided low-intensity behavioural activation intervention for people with dementia and depression in the Swedish healthcare context (INVOLVERA): a study protocol using codesign and participatory action research - Louise von Essen; Oscar Blomberg; Joanne Woodford; Chelsea Coumoundouros; Anna Cristina Åberg; Paul Farrand; Frida Svedin; Anders Brantnell (BMJ Open)
Introduction Dementia is a worldwide health concern with incident rates continuing to increase. While depression prevalence is high in people with dementia and psychological interventions such as cognitive behavioural therapy (CBT) are effective, access to psychological interventions remains limited. Reliance on traditional CBT for people with dementia and depression may present difficulties given it is a complex psychological approach, costly to deliver, and professional training time is lengthy. An alternative approach is behavioural activation (BA), a simpler psychological intervention for depression. The present study seeks to work with people with dementia, informal caregivers, community stakeholders, and healthcare professionals, to adapt a guided low-intensity BA intervention for people with dementia and depression, while maximising implementation potential within the Swedish healthcare context.Methods and analysis A mixed methods study using codesign, principles from participatory action research (PAR) and normalisation process theory to facilitate the cultural relevance, appropriateness and implementation potential of the intervention. The study will consist of four iterative PAR phases, using focus groups with healthcare professionals and community stakeholders, and semi-structured interviews with people with dementia and informal caregivers. A content analysis approach will be adopted to analyse the transcribed focus groups and semi-structured interviews recordings.Ethics and dissemination The study will be conducted in accordance with the Declaration of Helsinki and data handled according to General Data Protection Regulation. Written informed consent will be obtained from all study participants. In accordance with the Swedish Health and Medical Services Act, capacity to consent will be examined by a member of the research team. Ethical approval has been obtained from the Swedish Ethical Review Authority (Dnr: 2020-05542 and Dnr: 2021-00925). Findings will be published in an open access peer-reviewed journal, presented at academic conferences, and disseminated among lay and healthcare professional audiences.